Smart Device Switching Using Hand Gesture and IoT - Othaman, Muhammad Shahdan; Azami, Mohammad Alifhakim; Md.amin, Zulkarnain; Azhar, Muhammad Amirul Hafeez (Multidisciplinary Applied Research and Innovation, 2023)
Smart Switching Devices using Hand Gesture and IoT is designed for switching electrical devices using hand gesture and IoT system. The project has two types of devices namely main device and lighting control device where the main device consists of APDS9960, ESP32, NRF24L01, and 16x2 LCD while the lighting control device consists of Maker Uno, NRF24L01+Antenna, and SK6812 RGB LED. The main device is used to control the switching of the lighting control device depending on the instructions given by user either via hand gesture or Blynk application to control the switching of the lighting device.